GAMBARAN NILAI PEAK EXPIRATORY FLOW RATE (PEFR) PADA PASIEN ASMA YANG MENGIKUTI SENAM ASMA DI PEKANBARU - Zibetra, Fendro; Munir, Sri Melati; Bebasari, Eka (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAsthma is a chronic inflammatory associated with airway cause symptoms such as recurrent episodes of wheezing, breathlessness, chest tightness and coughing, especially at night or in the early days and it is reversible with or without treatment. Asthma gymnastic is one of the recommended exercise therapy to help the process of rehabilitation in patients with asthma. To determine the success rate, it is important to evaluate and monitor the effect of asthma gymnastic to lung fuction periodically, with Peak Expiratory Flow Rate (PEFR) examination by using Peak Flow Meter before and after doing gymnastic. This was a cross sectional descriptive study using the total sampling technique to know the overview of PEFR in asthma patients that following asthma gymnastics in pekanbaru. . This research has 32 samples. Result showed that asthma patients who followed gymnastics asma were in the age group 41-50 years old (37,5%), most commonly happened in female (75%), most common had not comorbidities (53,12%), most common patients had a family history of asthma (62,5%), the length of time following asthma gymnastics was the most ≥3 month (59,37%). The degree was the (37,5%). Assessment of asthma control was the most good controlled asthma (46,87%). Assesment of PEFR was the most low obstructive (43,75%).Key word : asthma, asthma gymnastic, Peak Expiratory Flow Rate (PEFR)